Assistance for Tasik Said Na'um Market traders through market duplication in facing the digital market - Maria Nino Istia; Tika Dwi Ariyanti; Sri Isti Untari; Kristin Lukitaningrum (Universitas Muhammadiyah Magelang, 2023)
Entrepreneurs at Tasik Tanah Abang Market require guidance and facility support to develop their businesses sustainably and increase profitability. This community service program aims to broaden their knowledge of online marketing tools through empowerment activities, enhancing accessibility in the digital market. By helping them understand the opportunities presented by online sales, the goal is to expand their sales and increase turnover. The implementation of this community service activity involves providing online selling through streaming, offering assistance with live selling techniques on social media, and promoting the market through video on social media platforms. The results of the activity indicate that providing support for traders through market duplication can yield significant benefits. Sales assistance with live selling also enhances traders' understanding of utilizing online platforms for product marketing. By creating additional distribution channels through digital markets, traders can expand their customer reach without neglecting the significance of traditional markets. This approach not only increases income but also contributes to economic sustainability for these entrepreneurs.